2010
DOI: 10.1007/s10236-010-0329-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tidal asymmetry and temporal settling lag on sediment trapping in tidal estuaries

Abstract: Over decades and centuries, the mean depth of estuaries changes due to sea-level rise, land subsidence, infilling, and dredging projects. These processes produce changes in relative roughness (friction) and mixing, resulting in fundamental changes in the characteristics of the horizontal (velocity) and vertical tides (sea surface elevation) and the dynamics of sediment trapping. To investigate such changes, a 2DV model is developed. The model equations consist of the widthaveraged shallow water equations and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
166
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 161 publications
(181 citation statements)
references
References 23 publications
(27 reference statements)
5
166
0
Order By: Relevance
“…Jay and Musiak (1994) and Sanford et al (2001) demonstrated that net sediment transport due to ebb-flood asymmetry in intensity of turbulence during a tidal cycle significantly affects the location of the turbidity maximum. A similar conclusion was made by Chernetsky et al (2010) with respect to net sediment transport that results from the interaction between the M 2 tide and external M 4 tide. Recent studies (Donker and de Swart 2013;Winterwerp et al 2013) stressed the role of flocculation and hindered settling in sediment trapping.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Jay and Musiak (1994) and Sanford et al (2001) demonstrated that net sediment transport due to ebb-flood asymmetry in intensity of turbulence during a tidal cycle significantly affects the location of the turbidity maximum. A similar conclusion was made by Chernetsky et al (2010) with respect to net sediment transport that results from the interaction between the M 2 tide and external M 4 tide. Recent studies (Donker and de Swart 2013;Winterwerp et al 2013) stressed the role of flocculation and hindered settling in sediment trapping.…”
Section: Introductionsupporting
confidence: 79%
“…Note that in contrast to previous studies (e.g. Huijts et al (2006) and Chernetsky et al (2010)), the equation is two-dimensional. Solutions are obtained by a novel iteration procedure, where in the initial step only the term involving the lateral sediment transport is considered.…”
Section: Solutionsmentioning
confidence: 76%
“…Consequently, Burchard and Baumert (1998) used a limited amount of sediment in their model to study the equilibrium dynamics of an ETM. In the analytical approach of Huijts et al (2006) and Chernetsky et al (2010), the inclusion of a spatially varying erosion coefficient is essential to describe the trapping of fine sediment in the lateral and longitudinal directions, respectively. Limited sediment availability is reflected by the observation that erodibility decreases with depth within the sediment layer and can be expressed as a critical shear stress increasing with depth (Sheng and Villaret 1989;Cartwright et al 2009;Dickhudt et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The focus on vertical processes, thereby ignoring horizontal gradients, is a reasonable approximation in many estuarine systems, since vertical exchange processes are typically dominant up to leading order (see, e.g. the scaling analysis 97 in the models of Chernetsky et al 2010;Dijkstra et al 2017).…”
Section: Model Equationsmentioning
confidence: 99%
“…Several studies have made this connection by using the combined knowledge of measurements and model results (Chernetsky et al 2010;De Jonge et al 2014;Van Maren et al 2015). A possible feedback mechanism that could result in such a transition was proposed by .…”
Section: Introductionmentioning
confidence: 99%